Respuesta :

Answer:

(6, 5 )

Step-by-step explanation:

Given the 2 equations

4x + 8y = 64 → (1)

7x - 2y = 32 → (2)

Multiplying (2) by 4 and adding to (1) will eliminate the y- term

28x - 8y = 128 → (3)

Add (1) and (3) term by term, that is

32x = 192 ( divide both sides by 32 )

x = 6

Substitute x = 6 into either of the 2 equations

Substituting x = 6 into (1)

4(6) + 8y = 64, that is

24 + 8y = 64 ( subtract 24 from both sides )

8y = 40 ( divide both sides by 8 )

y = 5

Solution is (6, 5 )

ACCESS MORE